2018
DOI: 10.1039/c7ib00179g
|View full text |Cite
|
Sign up to set email alerts
|

CD44v6 increases gastric cancer malignant phenotype by modulating adipose stromal cell-mediated ECM remodeling

Abstract: CD44, an abundantly expressed adhesion molecule, and its alternative splice variants have been associated with tumorigenesis and metastasis. In the context of gastric cancer (GC), de novo expression of CD44 variant 6 (CD44v6) is found in more than 60% of GCs, but its role in the pathogenesis and progression of this type of cancer remains unclear. Using a combination of media conditioning experiments and decellularized extracellular matrices (ECMs), this study investigates the hypothesis that CD44v6 overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Tumor-conditioned media (TCM) was prepared as previously described [ 16 ]. In brief, MKN74 and CD44v6 cells were cultured as above until 90% confluence, rinsed with phosphate buffered saline (PBS, pH 7.4), and then incubated with low serum media (DMEM, 1% FBS, 1% Pen/Strep).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor-conditioned media (TCM) was prepared as previously described [ 16 ]. In brief, MKN74 and CD44v6 cells were cultured as above until 90% confluence, rinsed with phosphate buffered saline (PBS, pH 7.4), and then incubated with low serum media (DMEM, 1% FBS, 1% Pen/Strep).…”
Section: Methodsmentioning
confidence: 99%
“…In the stomach, we have shown that CD44v6 is considerably de novo expressed in gastric pre-malignant and malignant lesions (more than 60% of all GCs), while the normal gastric mucosa remains negative for this marker [ 14 ]. Additionally, we have recently demonstrated that CD44v6 has been correlated with poor prognosis [ 15 ] and aggressive behavior of the disease [ 16 ], suggesting its value not only for early diagnosis but also for prognosis and as a therapeutic target in GC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decellularization was achieved as previously described. 12,58 Briefly, ASC cultures were washed with phosphate-buffered saline and subsequently incubated in 0.5% Triton-X þ 200 mmol/L NH 4 OH, 12,59,60 followed by incubation in 1 U/mL DNase (VWR Amresco, Radnor, PA) at 37 C to remove cellular membranes, organelles, and nucleic acids. After decellularization, maintenance of native matrix structure and key compositional components was confirmed by immunofluorescence analysis of Fn (Millipore-Sigma, St. Louis, MO; F7387) and collagen type I (Abcam; ab34710) via confocal microscopy (Zeiss, Pleasanton, CA; 710) and image analysis.…”
Section: Preparation Of the Decellularized Ecm Model Systemmentioning
confidence: 99%
“…Recently, some researchers have found that extracellular matrix (ECM) molecules, such as collagen proteins, laminins, and fibronectin, are pivotal for the progression of tumors, including breast cancer, pancreatic cancer, gastric cancer, glioma, and so on. And the ECM interaction pathway also can participate in the invasion of glioma, especially its role in regulating the mobility of the cells .…”
Section: Introductionmentioning
confidence: 99%